TEKNIK PENYUSUNAN ARAH DAN KEBIJAKAN UMUM APBD - Aban Subandi (UNIVERSITAS ISLAM SYEKH YUSUF, 2019)
In implementing regional autonomy in a broad, tangible, and responsible manner, budget reform is needed. The main aspect of budget reform is the budget of the traditional budget for the performance budget, and one component that must be developed within the framework of budget implementation is to compile the General Budget Directions and Policies. General directions and policies are a guideline for regional governments in carrying out various public service activities in order to effectively achieve their goals and objectives. APBD General Direction and Policy. Service components and expected level of approval in each area of authority. Local Government will carry out one fiscal year. Preparation of APBD Direction and General Policy, must consider the Regional Strategic Plan, the results of the evaluation of the performance of the previous period of the government, the main ideas of the Regional Budget and directions from the central government. Directions and APBD General Policies that are compiled must receive instructions and general provisions approved by the APBD. In the performance budget system, APBD Direction and General Policy besides being a budget planning instrument are also the basis for evaluating regional financial performance.